2003
DOI: 10.1063/1.1635983
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar surface deformation of sapphire: Numerical simulation of nanoindentation

Abstract: This report addresses the origin of peculiar anisotropic deformation of sapphire. The three-dimensional finite element simulation of the contact between spherical indenter and elastically anisotropic solid allowed us to analyze stress under the tip that penetrates in the (1010) and ͑0001͒ planes, and consequently, to localize those regions in which particular deformation mechanisms are likely to be activated. This approach contrasts the available models of ''hardness anisotropy,'' which routinely apply a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…Indeed, the results of ultrasonic measurements, FEM analysis and experimental values collected in Table 1 point towards the elastic and plastic anisotropy of YSZ crystal, similarly to the recent findings by Nowak et al [10,13] who reported different elastic behavior of sapphire before and after pop-in event. The obtained results (Table 1) consistently indicate the (1 0 0) surface as the one with the highest Young's modulus and the (1 1 1) surface with the lowest stiffness.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed, the results of ultrasonic measurements, FEM analysis and experimental values collected in Table 1 point towards the elastic and plastic anisotropy of YSZ crystal, similarly to the recent findings by Nowak et al [10,13] who reported different elastic behavior of sapphire before and after pop-in event. The obtained results (Table 1) consistently indicate the (1 0 0) surface as the one with the highest Young's modulus and the (1 1 1) surface with the lowest stiffness.…”
Section: Resultssupporting
confidence: 83%
“…We explored to certain extent the wide experience achieved with nanoindentation study of the Al 2 O 3 crystals [10][11][12][13], to conclude on both elastic and plastic anisotropy of the YSZ material, to discuss the pop-in event and dislocation activity. Moreover, the present authors performed the finite element (FEM) simulation of nanoindentation into different crystal planes to verify the mechanical characteristics obtained by nanoindentation measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The complete resolution of the observed phenomena and reliable evaluation of mechanical characteristics should involve 3D-FEM-aided inverse analysis of the indentation deformation of multilayer structure that already proved capable to treat similarly complex tasks (see e.g., [32][33][34][35]) or one of the fresh analytical approaches, e.g., [36].…”
Section: The Pop-in Event In Low-k Thin Filmsmentioning
confidence: 99%
“…The present research reviews the former approach and attempts to resolve the elasto-plastic behavior observed for GaN including the controversial singularities, so-called "pop-in events" that mark incipient plasticity [7][8][9][21][22][23][24][25][26]. We present high-accuracy nanoindentation experiments performed on the basal plane C (0001) of GaN with the tips of various shape.…”
Section: Introductionmentioning
confidence: 98%